(untitled) (Semiárida, 2020)
Juan Williamson Botanical Garden is located 7 km North of Santa Rosa (La Pampa) at the Faculty of Agronomy, UNLPam. The plant collection comprises a variety of species mostly cultivated at its foundation in 1974. In December 2016, a fire that burnt 85% of its area affected a large number of plants. The objective of this work was to carry out a postfire survey of plant collection losses in order to recommend the necessary actions for specimen’s replacement, and other actions for the full recovery of the burnt area. Surveys to identify species, number and condition of burned specimens were conducted 3, 15 and 21 months after the fire. The most affected collections were the Arboretum and the Teaching Garden with a total of 50 dead trees and shrubs specimens, corresponding to 31 taxa, mostly of the Cupressaceae Family. In order to guarantee the preservation of the JBJW didactic scientific historical heritage, recovery actions for plant collections affected by fire are recommended.